A case report of cryoballoon-based pulmonary vein isolation in a patient with situs inversus abdominalis and levocardia. Issue 7 (7th July 2021) - Anwar, Omar; Espersen, Tobias; Willems, Stephan; Eickholt, Christian
Abstract: Background: Cryoballoon-based pulmonary vein isolation (cbPVI) is a standardized treatment of atrial fibrillation. In complex anatomies, radiofrequency ablation (rfPVI) is usually preferred. We describe the first cbPVI in a rare patient with SI and levocardia. Case summary: A 41-year-old male patient with paroxysmal atrial fibrillation was referred to our clinic after a previous, unsuccessful cbPVI procedure. Observation of an atypical lead-wire position due to an abnormal anatomy of the inferior vena cava led to its initial termination. A subsequent thoraco-abdominal computed tomography revealed situs inversus abdominalis and levocardia and the procedure was re-attempted in our clinic. Transseptal puncture (TSP) was guided via transoesophageal echocardiography and fluoroscopy, using a SL0-Sheath and a standard BRK-needle. Advancement of the sheath initially failed but after additional dilatation with an Inoue ® dilator, transseptal passage of the sheath was successful. Due to the unusual antero-cranial TSP, the septal pulmonary veins (PV) contrasted poorly. After repeat TSP, a steerable FlexCath Advance ® sheath was introduced into the left atrium using an Amplatz Super Stiff ® guidewire. Subsequently, all PV were intubated with the Achieve ® catheter, over which a 2nd generation cryoballoon was introduced. Despite the practical challenges in this case, all PV were isolated. Discussion: The main challenges include the achievement of transseptal access and manipulation of the cryoballoon to achieve a patent seal of the pulmonary veins. cbPVI eliminates the need for constant re-positioning of the ablation catheter and might facilitate the creation of durable lesions under such difficult anatomical conditions.